Analisis Serapan Karbon Vegetasi dan Potensinya dalam Mereduksi Emisi CO₂ Kendaraan Bermotor di Jalan Dr. Ir. H. Soekarno, Surabaya - Criselli Naftalia, Hana; Amalia, Aussie (Jurnal Serambi Engineering, 2025)
Green belts play an important role in reducing greenhouse gas emissions in urban areas. This study aims to determine the total carbon stock and carbon absorption capacity of vegetation along the green belt of Dr. Ir. H. Soekarno IIC Road (MERR) in Surabaya, and to analyze the extent to which vegetation can reduce carbon dioxide (CO₂) and carbon monoxide (CO) emissions produced by motor vehicles. The method used in this study involves direct measurement of vegetation parameters such as tree diameter and height, which are then processed using biomass estimation and carbon stock conversion factors. In addition, CO₂ emissions are estimated based on traffic volume data and emission factors for each type of vehicle. The results show that the vegetation in the MERR IIC green belt is able to store a certain amount of carbon and has potential in absorbing CO₂ emissions, although it is still not proportional to the total emissions produced by motor vehicles per day. Therefore, improving the quality and quantity of vegetation in urban green belts is crucial to support air pollution control efforts in urban areas.